2015
DOI: 10.1182/blood-2014-04-572255
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic and in vivo comparison of diverse MSC sources reveals an endochondral signature for human hematopoietic niche formation

Abstract: Key Points Epigenetics and in vivo behavior can distinguish MSCs from different sources. BM-derived MSCs form a hematopoietic niche via a vascularized cartilage intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
238
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(251 citation statements)
references
References 49 publications
9
238
1
3
Order By: Relevance
“…Similarly, Noël et al [81] showed by microarray from Passage 1 (P1) BM-MSC and Ad-MSC that genes involved in chondro/osteogenesis, such as HES1, DLX5, TWIST1, BGLAP, OSX, SOX9, WNT5A, TGFΒ1 and VEGF were upregulated in BM-MSC. These results were confirmed recently in Reinisch et al [47] , which showed that genes related to chondro/osteogenesis such as RUNX2, RUNX3, BGLAP, MMP13, ITGA10, DLX5, DLX6, SPP1, BGLAP, ALPL, SPP1, COL2A, COL10A, and ACAN were upregulated in BM-MSC compared to Ad-MSC. The same researchers also confirmed that hemato/angiogenic genes such as INHBA, FZD1, TLR4, DGFC, ANGPT1, VEGFA, CTGF, and VEGFC were also upregulated in BM-MSC, confirming Brocher's results [42,47] .…”
Section: Bm-msc and Ad-msc Gene Signaturesupporting
confidence: 78%
See 3 more Smart Citations
“…Similarly, Noël et al [81] showed by microarray from Passage 1 (P1) BM-MSC and Ad-MSC that genes involved in chondro/osteogenesis, such as HES1, DLX5, TWIST1, BGLAP, OSX, SOX9, WNT5A, TGFΒ1 and VEGF were upregulated in BM-MSC. These results were confirmed recently in Reinisch et al [47] , which showed that genes related to chondro/osteogenesis such as RUNX2, RUNX3, BGLAP, MMP13, ITGA10, DLX5, DLX6, SPP1, BGLAP, ALPL, SPP1, COL2A, COL10A, and ACAN were upregulated in BM-MSC compared to Ad-MSC. The same researchers also confirmed that hemato/angiogenic genes such as INHBA, FZD1, TLR4, DGFC, ANGPT1, VEGFA, CTGF, and VEGFC were also upregulated in BM-MSC, confirming Brocher's results [42,47] .…”
Section: Bm-msc and Ad-msc Gene Signaturesupporting
confidence: 78%
“…The analysis of this literature underlines considerable variations between results obtained from different research teams that may be linked to the heterogeneity in (i) donors and donors' characteristics (e.g., health status, gender, age), (ii) in vitro/ex vivo protocols (e.g., sample isolation sites and methods, [33][34][35][36][37][38] , which represents the most robust comparison as they are not biased by inter-individual variabilities, in particular age, gender and health status. Nine studies comparing age-matched donors were also retained, which include 1 study on female donors only [39] , 1 study on 50% male and 50% female donors [40] , 2 studies on a close but not identical number of females and males [41,42] , and 5 studies on donors matched for age but without specifying the gender [43][44][45][46][47] . Finally, 4 studies compared the two types of MSC isolated from healthy donors, but with unknown age and gender [48][49][50][51] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Charles Chan has led our group in finding the mouse skeletal stem cell (SSC) that not only selfrenews but also gives rise at the single-cell level to osteocytes, chondrocytes, and up to four distinct marrow stromal cells (124). Placed under the kidney capsule in large cell numbers, SSCs form bone and cartilage in a morphologically correct manner (124)(125)(126)(127), with a bone marrow cavity containing host-derived HSCs and blood vessels. Of the stromal cell subsets, at least one was in the Whitlock clones (121), and at least three of the stroma support HSCs and hematopoiesis (124-127).…”
Section: Wwwannualreviewsorg • How One Thing Led To Anothermentioning
confidence: 99%